Mapping the circumnuclear regions of the Circinus galaxy with the Imaging X-ray Polarimetry Explorer - Ursini F; Marinucci A; Matt G; Bianchi S; Marin F; Marshall HL; Middei R; Poutanen J; Rogantini D; De Rosa A; Di Gesu L; Garcia JA; et al. (OXFORD UNIV PRESS, 2025)
We report on the Imaging X-ray Polarimetry Explorer (IXPE) observation of the closest and X-ray brightest Compton-thick active galactic nucleus (AGN), the Circinus galaxy. We find the source to be significantly polarized in the 2-6 keV band. From previous studies, the X-ray spectrum is known to be dominated by reflection components, both neutral (torus) and ionized (ionization cones). Our analysis indicates that the polarization degree is 28 +/- 7 per cent (at 68 per cent confidence level) for the neutral reflector, with a polarization angle of 18 degrees +/- 5 degrees, roughly perpendicular to the radio jet. The polarization of the ionized reflection is unconstrained. A comparison with Monte Carlo simulations of the polarization expected from the torus shows that the neutral reflector is consistent with being an equatorial torus with a half-opening angle of 45 degrees-55 degrees. This is the first X-ray polarization detection in a Seyfert galaxy, demonstrating the power of X-ray polarimetry in probing the geometry of the circumnuclear regions of AGNs, and confirming the basic predictions of standard Unification Models.